Analisis Blue Ocean Leadership Perusahaan Penanaman Modal Asing (PMA) di Indonesia - Kemal Al Kindi Mulya; Muhamad Raykhan Rahmatullah (Journal of Management and Bussines (JOMB), 2025)
This study aims to evaluate the leadership practices carried out by expatriate leaders in PMA companies in Indonesia and to formulate a new leadership model using the Blue Ocean Leadership (BOL) approach. The research method is a descriptive survey with a Likert scale questionnaire instrument and additional data from in-depth interviews with leaders and key staff. The findings show that current practices are still not optimal and have not fully focused on key leadership activities according to BOL, so that several problems such as SOP violations, distrust, and lack of transparency still often occur. Based on this analysis, three main strategies are proposed within the BOL framework: eliminating excessive intervention in operations, improving vision communication and cross-cultural training, and developing a daily performance-based reward system to increase motivation and transparency. The implications of this study provide practical recommendations for PMA companies in maximizing the effectiveness of cross-cultural leadership and creating an innovative work environment to improve the performance and engagement of local employees.   Keywords: Blue Ocean Leadership, Cross-Cultural Leadership, Expatriate Leadership